Parental selection for the formation of interspecific hybrid populations of oil palm - Peixoto, Leonardo de Azevedo; Bhering, Leonardo Lopes; Gurgel, Fábio de Lima; Gomes Junior, Rui Alberto (Acta Scientiarum. Agronomy, 2013)
The objective of this work was to select families with superior performance and large genetic variability for diallel crosses for potential use in the pre-breeding of oil palm. The experiment consisted of 42 full-sib families divided into three trials with 16 families and 3 witnesses in common in randomized blocks, with four blocks and 12 plants per block. The characteristics evaluated in the experiment were number of bunches per plant (NBP), bunch weight per plant (BWP) and bunch average weight per plant (BAW). The estimation of variance components showed that there was greater genetic variance within families than between families. The heritability for all traits was high, above 0.75, and the coefficient of environmental variation was low to moderate for all traits (between 4 and 13). Tocher’s method separated families into seven groups, whereas the UPGMA method identified six groups. To use the best families in diallel crosses, families 15, 14, 22, 21, 28, 37, 33 and 39 were selected based on individual performance as determined by the Scott-Knott test and genetic diversity by grouping.

O objetivo deste trabalho foi selecionar famílias com desempenho superior e ampla variabilidade genética para cruzamentos dialelos e com potencial utilização no pré-melhoramento de dendê. O experimento consistiu em 42 famílias de irmãos completos, divididas em três ensaios com 16 famílias e 3 testemunhas comuns, sendo estes em delineamento em blocos ao acaso com quatro blocos, e 12 plantas por bloco. As características avaliadas no experimento foram número de cachos por planta (NCP), produção de cachos por planta (PCP) e peso médio de cacho (PMC). Com estimação dos componentes de variância verificou-se que existe uma maior variância genética dentro de famílias do que entre famílias. A herdabilidade para todas as características foram altas, acima de 0,75 e o coeficiente de variação ambiental encontrado para todas as características foi de baixo a moderado (entre 4 e 13). As famílias foram separadas em sete grupos pelo método de Tocher e em seis grupos com o método UPGMA. Visando a utilização das melhores famílias em cruzamentos dialelos, as famílias 15, 14, 22, 21, 28, 37, 33 e 39 foram selecionadas com base na performance individual, através do teste de Scott-Knott, e diversidade genética através do agrupamento.
Keywords: Elaeis guineensis; Cluster analysis; Genetic diversity